Representaciones sociales del cuerpo y la sexualidad en serumistas y su vínculo con la atención médica - Munive Rodríguez, Andrea (2022)
The purpose of this research is to know the representations around the body and sexuality in young doctors serving in the SERUMS, in order to reveal their links with medical attention. This research is of a qualitative nature, to the extent that it is proposed to analyze the subjectivities and constructions of serumists. The findings of this research point out that in the midst of the influence of medical training, marked by a biologist tradition, serum specialists have a degree of agency through which they are able to articulate what is taught in different contexts, develop criticism and select those logics and notions that help them in their understanding of reality and self-produce their own meanings around certain elements. However, sometimes there is a tendency to reproduce practices linked to disparities in the doctor-patient relationship, as well as in geographical and epistemological dimensions.